2009
DOI: 10.1111/j.1467-2979.2008.00298.x
|View full text |Cite
|
Sign up to set email alerts
|

Can circle hook use benefit billfishes?

Abstract: We performed a quantitative review to evaluate circle hook use in recreational and commercial hook-and-line fisheries that interact with billfishes (Family: Istiophoridae). Specifically, we scrutinized the findings of 11 recent empirical studies that reported, on a species-specific basis, side-by-side measures of circle vs. J-hook fishing performance: catch, mortality, deep-hooking and bleeding rates. Of the 30 total comparisons extracted from the literature that satisfied our inclusion criteria, 13 indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 21 publications
3
42
0
Order By: Relevance
“…Tuna and teracima hooks have a slightly curved shaft, and like J-hooks, the shaft does not protect the point, and as a result, are categorized as 'J-shaped' hooks ( Fig. 1) (Beverly and Chapman 2007;Serafy et al 2009). Circle hooks are circular or oval shaped, and the point is turned perpendicularly back toward the shank, making the point less exposed relative to J-shaped hooks.…”
Section: Hook Shapementioning
confidence: 99%
“…Tuna and teracima hooks have a slightly curved shaft, and like J-hooks, the shaft does not protect the point, and as a result, are categorized as 'J-shaped' hooks ( Fig. 1) (Beverly and Chapman 2007;Serafy et al 2009). Circle hooks are circular or oval shaped, and the point is turned perpendicularly back toward the shank, making the point less exposed relative to J-shaped hooks.…”
Section: Hook Shapementioning
confidence: 99%
“…Circle hooks in 28 studies of marine recreational fisheries indicated an overall tendency for lower mortality, as circle-hooked fish were more frequently jaw-hooked than deep-hooked (Cooke and Suski, 2004). A quantitative review (Serafy et al, 2009) of 11 istiophorid studies of circle and J-hook performance in recreational rod-and-reel and commercial longline fisheries provided 30 species-specific comparisons, with 13 statistically significant differences between hook types. No significant differences in catch rates were evident for 4 billfishes (striped, white, blue marlin and sailfish) among 9 comparisons.…”
Section: Introductionmentioning
confidence: 97%
“…1; Cooke and Suski, 2004;Serafy et al, 2009). Circle hooks have been promoted in swordfish longline fisheries (Watson et al, 2005;Gilman et al, 2007; see review by Read, 2007) because of these hooks' potential to reduce sea turtle interaction rates, and they have a higher frequency of mouth hooking vs. deep hooking for sea turtles and fishes, which may reduce post-release mortality.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…;soykan et al 2008). although longlines are more selective than other fishing gears (e.g., trawls), drifting pelagic longlines catch a wide variety of bycatch, the unintended non-target organisms that are captured during fishing operations (lewison et al 2004).…”
mentioning
confidence: 99%